Accelerating positive change in electronic records management - McLeod , Julie; Childs , Sue; Hardiman , Rachel (Archives & Manuscripts, 2011)
This article outlines 10 headline findings from a three-year multidisciplinary project, funded by the UK Arts and Humanities Research Council, on electronic records management (ERM). It also presents examples of solutions to try, or to avoid, grounded in experience. A range of strategies and tactics exist and, although their relevance and success is very contextualised, they could be adopted or adapted in many scenarios. The findings highlight the complexity of the ERM challenge, the Interrelationship of people, processes and systems/technology, and the predominant and powerful role of people in accelerating positive change, or not. Two strategic conclusions are drawn which are particularly important for records professionals to address: (1) the need to articulate a vision of successful ERM and (2) the need to reinterpret records management principles in the electronic environment.